Kesejahteraan Ekonomi Petani Tradisional Bawang Merah di Sukomoro Pada Masa Pandemik Covid-19 - Lavenia Gita Perdana Sari; Jaka Nugraha (Universitas Negeri Surabaya, 2021)
The Covid 19 pandemic, which has lasted for approximately nine months in Indonesia, is considered to have an impact on the prices of agricultural products, especially horticultural products and livestock products. The Indonesian Political Economy Association (AEPI), assessed that the two products were the most disturbed, especially in relation to the absorption of their production during the pandemic. One type of horticultural product that has been affected by the Covid-19 pandemic is onion. This study aims to analyze the economic welfare of traditional onion farmers in Sukomoro during the Covid-19 pandemic. The research method used is descriptive qualitative method with data collection through interview techniques. Based on the research results, the conclusion that can be drawn is that the level of welfare of onion farmers in Sukomoro Village during the Covid-19 pandemic was also affected. According to the results of research in the field before the Covid-19 pandemic, the informants' family income level can be said to be sufficient, they can buy food, clothing and also make a house for their family. All of their children can also go to school from the income from onion farming. Although there was a reduction in income due to reduced sales and rotting onion stocks. However, in general, his welfare condition is still good. This can be seen from the conditions of residence, education, and the ability to provide for family members.